Peranan Cagar Budaya Megalitik Palindo dalam Pengembangan Sektor Pariwisata di Kecamatan Lore Barat Kabupaten Poso Provinsi Sulawesi Tengah - Yomba, Andini Gracia; Zuraidah, Zuraidah; Kristiawan, Kristiawan (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025), 2025)
Lore Barat has a megalithic icon called the Palindo Megalithic. The Palindo Megalithic as cultural heritage start from 14 August 2023 because they have uniqueness and historical value. This research aims to determine the role of the Palindo Megalithic cultural heritage for developing the tourism sector and strategies of Palindo Megalithic in developing the tourism sector. This research use method such as observation, interviews and literature study. Data analysis used qualitative analysis and SWOT analysis to help answer questions from the problem formulation. Based on the results of the analysis of the Palindo Megalithic cultural heritage, it has a role in developing the tourism sector, such as being a tourism icon, developing MSMEs and preserving traditional traditions. The strengths of the Palindo Megalithic are: uniqueness, historical value, and cultural tourism activities. Weaknesses that are accessibility and facilities, design still havennt managed optimally, funding from the government is lacking/inhibited, and low levels of human resources. Look at the potential, it has opportunities such as local economic development. The forms of threat based on field observations can be divided into two: natural factors and human activity factors